SYMBOL AS THE ACTUALIZATION OF TRANSCENDENTAL IN AVIATION ART TUNING - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The problem of constructing a symbolic representation aviation community factors based on religious worldview